THE DEVELOPMENT OF COMPUTER PROGRAMMING COMPETENCY OF PRATHOMSUKSA FOUR STUDENTS USING PROBLEM BASED TEACHING AND LEARNING - Chaihoy, Keadtisuk; Wanpen, Supatra; Jansrisukot, Julamas (Journal of Humanities, Social Sciences, and Arts, 2023)
Abstract The purpose of this research was to compare computer programming competency of Prathomsuksa 4 Students in a school under the jurisdiction of the Nong Khai Primary Educational Service Area Office to the 80 percent criterion after receiving problem-based instruction and learning. 20 Prathomsuksa 4 students were selected to be samples of the study using cluster random sampling method. The research design was a one group pretest - posttest design. The research instruments included learning management plans to develop computer programming abilities, a computer programming cognitive test, and an observation form for evaluating practical programming skills. Statistics used for data analysis were mean, percentage, standard deviation, one-sample t-test, and dependent samples t-test. The findings revealed that Prathomsuksa 4 students who received problem-based instruction exhibited higher scores in computer programming competency after the learning intervention, surpassing the predefined criterion of 80 percent at the significant level of 0.01